(3GdHjFI hLfGM GdCMOGK (B:s (3OQGSI GLJeGYjI ejOGfjI dYjfI ef GdCMOGK GdLGfMjf hZjQ GdLGfMjf (B/s - (3eMeO, haGA eMeO Ydj,s 1967- ((3GdbGgQI (B:s (3GdecJH GdYQHj ddeYGQa,s, 2014)
(3JMJhj gPg GdOQGSI Ydi HGHjf jJVefGf SHYI aUhd (B: (3GdHGH GdChd YHGQI Yf GdeONd GdfXQj ddOQGSI, hjfbSe gPG GdHGH Edi KdGKI aUhd, hCeG GdHGH GdKGfj ef gPg GdOQGSI ajYQV NWg GdOQGSI GdejOGfjI hfJGFLgG, hjJVef gPG GdHGH CQHYI aUhd(B. (3hCNjQG JfJgj GdOQGSI HNGJeg JfGbT HEjLGR Cge GdfJGFL GdJj fhbTJ JaUjdG aj KfGjG gPg GdOQGSI, hbO cTaJ fJGFL GdOQGSI Yf hLhO YdGbI Hjf GdSdhc GdLGfM hHjf HYV GdeJZjQGJ Ch GdYhGed GdCSQjI(B. s
(3HHdjhLQGajI (B: (3UaMI (B203-209.s
Keywords: (3LfGM GdCMOGKs -- (3LhGfH GLJeGYjIs; (3GdHjFI hGdEfSGfs